Pest categorisation of Cadang‐Cadang viroid. (18th July 2017) - ,; Jeger, Michael; Bragard, Claude; Caffier, David; Candresse, Thierry; Dehnen‐Schmutz, Katharina; Gilioli, Gianni; Gregoire, Jean‐Claude; Jaques Miret, Josep Anton; MacLeod, Alan; Navajas Navarro, Maria; Niere, Björn; et al.
Abstract: The EFSA Panel on Plant Health performed a pest categorisation of Cadang‐Cadang viroid for the European Union (EU) territory. Coconut cadang‐cadang viroid (CCCVd) is a well‐known viroid for which efficient molecular detection assays are available. It is transmitted by vegetative multiplication of infected hosts, by seed and pollen and, possibly, by the action of unknown vector(s). CCCVd is reported from a few countries in Asia and is not known to occur in the EU. It therefore does not meet one of the criteria for being a Union regulated non‐quarantine pest. The host range of CCCVd is restricted to Arecaceae species (palms), in particular coconut and it is listed on all known hosts in Annex IIAI of Directive 2000/29/EC. CCCVd is expected to be able to enter in the EU and to be able to establish in the open in the southernmost regions of the EU and elsewhere under protected cultivation. It has the potential to subsequently spread via plants for planting and possibly other mechanisms. CCCVd is able to cause severe symptoms in some Arecaceae species while others seem less affected. The potential impact of CCCVd if introduced in the EU is very difficult to assess. Given that the spread potential is, as for other viroids, likely to be limited, the potential impact is estimated to be limited in extent but this judgement is affected by large uncertainties. Overall, CCCVd meets all the criteria evaluated by EFSA to qualify as Union quarantine pest. The main knowledge gaps concern (1) the relationships between CCCVd‐related RNAs and CCCVd, (2) the origin and volume of the trade in palm seeds and plants for planting imported in the EU (3) the efficiency of natural spread under EU conditions and (4) host status and susceptibility of many palm species grown in the EU.